PENINGKATAN DAYA SAING MELALUI PERBAIKAN PERHITUNGAN HARGA POKOK PRODUKSI INDUSTRI KERIPIK DAN SEJENISNYA - Rasdianto; Nurzaimah; Mutia Ismail; Ricky Ary Syahputra (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2017)
Dedication held at Jl. Gaperta, Village Central Helvetia, district of Medan Helvetia, Medan, North Sumatra. Dedication took the title "Increasing Sales Through Improved Calculation of Cost of Production Industry Chips and Peyek". Community service will be made to the two businessmen households of preliminary surveys noting that the two housewives who do it faces constraints in which the products can not be marketed in the modern market or supermarkets because they do not have permission from the Ministry of Health (PIRT) and yet have the certificate Halal and requires few tools left to run the business that has been running for about four years and the effort the other household else has run the business for longer than the others which is about nine years had several employees freelance help in producing products that already have a name of "Kartika" which already has a permit Din Kes port on 215127501152 and already has a certificate from the Halal MUI no; 090100891110 has six types of products namely: cheese potato chips, cheese potato chips, carrot chips cheese, peanut dent, dent dent anchovies and spinach, facing obstacles unavailability of machines to grind boiled carrots and tools to attenuate the dough in bulk for processing production. Service to the community team will strive to help business partners for the constraints that it faces so as to produce a better business. Goal mono community service activities this year is expected to develop a business venture partner that had only done penjulan in traditional markets and by booking with a permit from the Department of Health and halal certificate from MUI venture partner product can be sold in modern markets or in supermarkets and mall- mall that is around the city of Medan and in turn will expand to other cities in North Sumatra